1980
DOI: 10.1111/j.1365-2125.1980.tb05847.x
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of drug dosage intensity in MVPP therapy in Hodgkin's disease.

Abstract: The dose of combination chemotherapy in Hodgkin's disease is commonly calculated from a formula based on the body surface area. A method is described for measuring the intensity of combination chemotherapy actually received compared to the calculated planned dose. The technique is applied to 56 patients receiving mustine, vinblastine, procarbazine and prednisolone, but would also be suitable for other cytotoxic regimens. The planned dosage intensity had to be significantly reduced in over half of the patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0
6

Year Published

1985
1985
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(18 citation statements)
references
References 7 publications
1
11
0
6
Order By: Relevance
“…In the current study the mean dose level achieved was 76%. This dose level is comparable to achieved dose levels re ported in the literature for MOPP or MOPP variants [16][17][18]. In this regard it is of interest to note that Bonadonna et al [16] found that higher dose levels could be achieved using MOPP/ABVD.…”
Section: Discussionsupporting
confidence: 67%
“…In the current study the mean dose level achieved was 76%. This dose level is comparable to achieved dose levels re ported in the literature for MOPP or MOPP variants [16][17][18]. In this regard it is of interest to note that Bonadonna et al [16] found that higher dose levels could be achieved using MOPP/ABVD.…”
Section: Discussionsupporting
confidence: 67%
“…Jednym z czynników potencjalnie wpływających na skuteczność pooperacyjnej chemioterapii u chorych na raka piersi jest jej intensywność, określana jako ilość leku podana w jednostce czasu [1][2][3]. Zarówno dane z badań retrospektywnych, jak i wyniki prospektywnych badań klinicznych wskazują, że należy unikać pochopnego zmniejszania dawek chemioterapii lub stosowania dawek niższych niż standardowe.…”
Section: Wstępunclassified
“…Recently the impact of the amount of drug delivered per unit time or dose intensity has been analysed (Green et al, 1980). A doseeffect relationship according to dose intensity has been shown in animal experimentation and in human pathology, especially in stage II breast cancer , in advanced breast cancer (Hryniuk & Bush, 1984;, in advanced ovarian cancer and in Hodgkin's disease (HD) (DeVita et al, 1987;Green et al, 1980).…”
mentioning
confidence: 99%
“…Recently the impact of the amount of drug delivered per unit time or dose intensity has been analysed (Green et al, 1980). A doseeffect relationship according to dose intensity has been shown in animal experimentation and in human pathology, especially in stage II breast cancer , in advanced breast cancer (Hryniuk & Bush, 1984;, in advanced ovarian cancer and in Hodgkin's disease (HD) (DeVita et al, 1987;Green et al, 1980). In the latter, the efficiency of MOPP-therapy (six courses) in advanced stage HD significantly correlates with the rate of delivery of vincristine (Longo et al, 1980), a reduction of over 65% of nitrogen mustard (Carde et al, 1983) and the suppression of prednisone (British National Lymphoma Investigation, 1975).…”
mentioning
confidence: 99%